Nurse-identified patient care and health services research priorities in the United Arab Emirates: a Delphi study - Nabeel Al-Yateem; Muna Al-Tamimi; Maria Brenner; Hanan Al Tawil; Alaa Ahmad; Sharon Brownie; Shameran Slewa-Younan (BMC, 2019)
Abstract Background The need for improved research on ill health has been recognized internationally and locally in the United Arab Emirates (UAE). The UAE Nursing and Midwifery Council recently committed to enhancing the status and contributions of nursing in healthcare research across the UAE by establishing a National Committee for Research Development. This study using a Delphi method to identify research priorities from the perspective of nurses delivering frontline healthcare. Methods A two-phase Delphi design was implemented with 1032 nurses participating in phase one of the study and 1339 in phase two. Results The most important priority was patient safety and healthcare professionals' awareness of international patient safety goals (including staffing levels and shift length) and potential effects on patient safety. Other important priorities were infection control practices and management of communicable diseases. Conclusions These priorities may inform nursing research programs to improve patient care and health outcomes in the UAE and similar contexts worldwide.